Governing networks in tourism: what have we achieved, what is still to be done and learned? - Volgger, Michael; Pechlaner, H. (Emerald Group Publishing Limited, 2015)
Purpose – Networks and networking are ubiquitous concepts in tourism, their importance appreciated by scholars and practitioners. Tourism research has developed elaborate methods and concepts to grasp the numerous variants of tourism networks and to gain insights into their governance. In particular, Association Internationale D’Experts Scientifiques Du Tourisme (AIEST) and its official journal, Tourism Review, have made significant contributions to the achievements in this research area. After approximately two decades of intensive research on tourism networks, it is appropriate to pause for a moment to critically assess the results achieved, to compare them with partly old, partly newly, emerging real-world challenges, and to explore future directions. Design/methodology/approach – This paper provides a selective and critical overview of the state-of-the-art in research on governing networks in tourism. This overview of eight major achievements is combined with an exploratory, comparative analysis of qualitative interviews with tourism practitioners. Findings – Considering the two sources mentioned above, the study derives seven suggestions for future directions in research on network governance in tourism. These relate to the big picture of tourism governance, e-governance, disparities within networks, negative aspects of networking, dynamism of networks, network moderators and means of network steering. Originality/value – Due to its design, the paper is uniquely able to compare real-world issues with up-to-date theoretical achievements, and will contribute to bringing them closer together in future approaches. Hence, it is relevant for both academic readers and practitioners.